A comprehensive evaluation of athletes professional skills based on fuzzy theory - Hou, Z. (BioTechnology: An Indian Journal, 2014)
The selection and training of excellent athletes is an important task for China. The scientific selection and evaluation of athletes is a key component of the training system of athletes. However, in China, many sports don`t have complete standards of selecting athletes. What`s more, the different levels of different athletes` comprehensive skills are about the comprehensive fuzzy concept. So it is difficult to work out an appropriate way of evaluating athletes. This paper analyzes the concept of fuzzy theory and the application of fuzzy theory in the comprehensive evaluation of athletes` professional skills, then uses fuzzy quantitative theory to establish an evaluation method and model of athletes` professional skills to quantify athletes` skills, and provide an effective method of training and selecting excellent athletes.